2016 7th International Conference on the Network of the Future (NOF) 2016
DOI: 10.1109/nof.2016.7810136
|View full text |Cite
|
Sign up to set email alerts
|

Post-resource sharing power allocation in cellular networks to coexist with D2D underlay

Abstract: Device to Device communications (D2D) is considered as a key technology component in fifth generation (5G) of mobile communication, which anticipates higher user density and traffic volume than in present. D2D communication aims to offload base station from traffic routing by enabling direct link between communicating devices in proximity. D2D underlay allows a D2D pair to reuse resources with a cellular link, leading to better spectrum utilization. However, D2D transmission causes significant interference to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…It has been shown that the performance of the cellular network is affected by the interference caused by D2D communication. The work in [8] proposed a post-resource allocation and power control scheme for cellular users. Frequency reuse scenario is determined based on the interference generated by the D2D users.…”
mentioning
confidence: 99%
“…It has been shown that the performance of the cellular network is affected by the interference caused by D2D communication. The work in [8] proposed a post-resource allocation and power control scheme for cellular users. Frequency reuse scenario is determined based on the interference generated by the D2D users.…”
mentioning
confidence: 99%